Corporate secrecy: the final barrier to corporate governance. (31st March 2006) - Chambers, Robert
Recent improvements in corporate governance such as SOX in the USA will not prevent the reoccurrence of corporate disasters such as Enron. The final barrier to effective corporate governance is corporate secrecy, and boards of directors working alone are unable to solve the problem. The solutions to corporate secrecy entail enhanced transparency and deterrence accompanied by elimination of the tools of corporate secrecy.